Faith and Theology : Praise of Via Eminentiae (Teología, 2019)
At the time of the New Evangelization, this text shows the importance of conversion as an essential part of theology’s reflective task. The author relates the efficacy of the theological word in dialogue with the actual postmodern culture, with the requirement – for theology – to overcome critically its own possible idolatries, entering decisively and joyfully into the via eminentiae: on the endless way towards “the all greater God”, a way which is at the same time towards the authentically human. The journey of the apostle Paul illustrates, in an exemplary way, the author´s approach.
Keywords: Theology; Conversion; Via Eminentiae; Deconstruction